1979
DOI: 10.1159/000232287
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rat Mast Cell Degranulation and Histamine Release by Histamine-Rat Gammaglobulin Conjugate

Abstract: Histamin-rat γ-globulin conjugate inhibited degranulation and histamine release of rat peritoneal mast cells to a greater extent than the rat globulin or histamine alone. Since mast cells contain histamine receptors, it may be assumed that the histamine bound to the γ-globulin combines with the rat mast cell histamine receptor and inhibits the degranulation and histamine release by a feedback mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Ishikawa et al [8] reported that this inhibits his tamine release and degranulation of mast cells in rats. In addition, histamine inhibits histamine release from baso phils through H2 receptor on the surface of the target cells [9], Similarly, Tanizaki etal.…”
Section: Discussionmentioning
confidence: 97%
“…Ishikawa et al [8] reported that this inhibits his tamine release and degranulation of mast cells in rats. In addition, histamine inhibits histamine release from baso phils through H2 receptor on the surface of the target cells [9], Similarly, Tanizaki etal.…”
Section: Discussionmentioning
confidence: 97%
“…IVIg could also bind to histamine and block histamine activation of MC as seen in rats. 16 An additional trigger for MC activation includes T-cell activity and release of microparticles and cytokines. 17 IVIg increases regulatory T-cells which could reduce T-cell activity and thereby reduce MC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also ASHIDA et al [29] recently reported that histamine at a concentration of 0,1 mM had no effect on cAMP levels in rat peritoneal mast cells. However, the finding by ISHIKAWA et al [30] that histamine or more specifically histamine-rat gammaglobulin conjugate inhibits rat mast cell degranulation, is at variance with this. A possibility exists that as in canine pulmonary airways [31], different rat strains have different numbers of H2-receptors on their mast cells.…”
Section: Speciesmentioning
confidence: 96%